Baseline predictors of visual acuity and retinal thickness outcomes in patients with retinal vein occlusion: Standard Care Versus COrticosteroid for REtinal Vein Occlusion Study report 10 - Scott, Ingrid U; VanVeldhuisen, Paul C; Oden, Neal L; Ip, Michael S; Blodi, Barbara A; Hartnett, Mary Elizabeth; Cohen, Geoff (Ophthalmology (Rochester, Minn.), 2011)
To investigate baseline factors associated with visual acuity and central retinal thickness outcomes in patients with macular edema secondary to retinal vein occlusion in the Standard Care versus COrticosteroid for REtinal Vein Occlusion (SCORE) Study. Two multicenter, randomized clinical trials: one evaluating participants with central retinal vein occlusion (CRVO) and one evaluating participants with branch retinal vein occlusion (BRVO). Participants with follow-up data of 1 year or more, including 238 with CRVO and 367 with BRVO. Visual acuity was measured by the electronic Early Treatment Diabetic Retinopathy Study (E-ETDRS) method, and central retinal thickness was measured by optical coherence tomography (OCT). Regression analysis related these outcomes to 20 baseline measures. Multiple P values were adjusted to control the false discovery rate. Outcome measures of visual acuity letter score included absolute change from baseline, a gain of ≥ 15 from baseline, and a loss of ≥ 15 from baseline. Outcome measures of center point thickness included absolute change from baseline, a measurement of ≤ 250 μm, and a measurement of ≥ 500 μm. Outcomes were assessed at 1 and 2 years. For CRVO and BRVO, younger age was associated with improved visual acuity and central retinal thickness outcomes. For CRVO, triamcinolone treatment and less severe anatomic abnormalities of the retina (center point thickness and areas of retinal hemorrhage, thickening, and fluorescein leakage) were predictive of better visual acuity outcomes. For BRVO, no history of coronary artery disease was predictive of improved visual acuity outcomes. For center point thickness outcomes, shorter duration of macular edema was associated with improvement in both disease entities. For CRVO, higher baseline visual acuity letter score was predictive of favorable OCT outcomes. For BRVO, lower baseline visual acuity letter score, presence of dense macular hemorrhage, and no prior grid photocoagulation were predictive of favorable OCT outcomes. Several factors were predictive of better visual acuity outcomes and more favorable OCT outcomes, including younger age and shorter duration of macular edema, respectively. These factors may assist clinicians in predicting disease course for patients with CRVO and BRVO.